Polysemic Nature of the Notion of Customer Capital of the Enterprise - T.O. Zavalii (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The analysis of English variants of capital names is created, due to relations and links of the enterprise with its customers has been conducted. There are three main terms «relational capital», «customer capital», «customer equity» that have become the subject of research. It is established that relational capital as a component of intellectual capital has an intangible nature and is created due to the relations of the enterprise with all its stakeholders. Customer capital as a component of the relational capital of an enterprise also has an intangible nature and is due to relations with customers. Instead, under the term «customer equity», which is similarly translated into Ukrainian as a customer capital, we understand its calculation model, based on the customer lifetime value. It has been found that in the course of its development, customer capital from customer-orientation has expanded its attention to all of the stakeholders of the company, thus causing the emergence of customer capital in the broad sense, also called relational or stakeholder.